2016
DOI: 10.1007/s00261-016-0897-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT texture analysis for evaluating histologic grade of urothelial carcinoma

Abstract: CTTA proved to be a feasible tool for differentiating LGUC from HGUC. MPP quantified from fine texture scale on unenhanced images was the optimal diagnostic parameter for estimating histologic grade of urothelial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 29 publications
0
27
1
Order By: Relevance
“…A radiomics approach has the potential to act as a noninvasive tool to assist in preoperative grading of urothelial cancer. But the sample size of these studies is small, and as UTUC is quite rare compared to bladder cancer, only our group and Mammen et al have included UTUC [14,15]. More data should be gathered to further evaluate the ability of radiomics for predicting pathological grade, especially in UTUC.…”
Section: Evaluation Of Pathological Gradementioning
confidence: 99%
See 1 more Smart Citation
“…A radiomics approach has the potential to act as a noninvasive tool to assist in preoperative grading of urothelial cancer. But the sample size of these studies is small, and as UTUC is quite rare compared to bladder cancer, only our group and Mammen et al have included UTUC [14,15]. More data should be gathered to further evaluate the ability of radiomics for predicting pathological grade, especially in UTUC.…”
Section: Evaluation Of Pathological Gradementioning
confidence: 99%
“…A few studies have explored the feasibility of texture analysis, machine learning and radiomics to distinguish between low-and high-grade urothelial cancer. A study by our group in 105 patients with urothelial carcinoma found that low-grade tumors demonstrated lower texture features of mean, entropy and mean of positive pixels (MPP) quantified from CT images and MPP could differentiate low-from high-grade tumors with an area under the curve (AUC) of 0.779 [14]. Mammen et al performed a similar texture analysis of CT scans of 48 patients with UTUC and found entropy was also greater in high-grade tumors with an AUC of 0.83 [15].…”
Section: Evaluation Of Pathological Gradementioning
confidence: 99%
“…Zhang et al showed that CT texture analysis proved to be a feasible tool for differentiating low-grade UC from high-grade UC. 23 Further examinations in many cases are necessary to verify the utility of these methods and establish a preoperative prediction system.…”
Section: T2 or Lower Stages Versus T3 Or Higher Stagesmentioning
confidence: 99%
“…Whether texture analysis is useful for diagnosis of >T2 disease remains unknown and requires further study. In addition to tumor stage, radiomic features have been found to provide information on tumor grade and disease aggressiveness, factors that impact both medical and surgical management . DCE‐derived tumor washout may be associated with higher‐grade cancer and quantitative ADC values have been shown to inversely correlate with tumor grade .…”
Section: Radiomic Analysismentioning
confidence: 99%
“…In addition to tumor stage, radiomic features have been found to provide information on tumor grade and disease aggressiveness, factors that impact both medical and surgical management. 93,[95][96][97] DCE-derived tumor washout may be associated with higher-grade cancer 93 and quantitative ADC values have been shown to inversely correlate with tumor grade. 92 Combining ADC values with different texture features (including entropy and kurtosis) shows promise for predicting higher-grade bladder cancer, although further work is needed to verify the results from these preliminary studies.…”
Section: Radiomic Analysismentioning
confidence: 99%